Penal populism: negotiating the feminist agenda. Evidence from Spain and Poland - Grzyb, Magdalena (European journal of criminology, 2021)
It is interesting to observe how penal populism intersects with feminism when it comes to gender-based violence, as regards both anti-rape and domestic abuse reforms. There is a vast scholarship (Bumiller, 2008; Gottschalk, 2006; Gruber, 2007) in the US explaining how feminist activism turned to state power to demand more protection and more criminalization, and little focus on the European context.